Optical properties of thin hexagonal boron nitride layers - Soltani, Ali; Bakhtiar, Hazri; Thevenin, Philippe; Bath, Armand (Faculty of Science, UTM, 2003)
Thin films of hexagonal boron nitride have been deposited at low temperature in a microwave plasma enhanced chemical vapor deposition reactor. They have been characterized by Infrared (FTIR) and micro-Raman spectroscopy (SMR). The films are optically anisotropic, and the IR measurements can be properly modelized when using an uniaxial model for the layers. This description is valid at the macroscopic scale, but gives only an averaged response of the polycrystalline nature of the films. Actually, they are constituted at the atomic scale by a collection of nanocrystallites with a preferred orientation around the normal of the layer. The size of the crystallites can be evaluated by micro-Raman measurements, when taking into account a confinement model. Some thermal annealing have been performed.